Pengaruh Partisipasi Anggaran Pada Senjangan Anggaran Dengan Tight Budget dan Locus Of Control Sebagai Pemoderasi - Wiradiputra, Nyoman July; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 25 No 1 (2018)DO - 10.24843/EJA.2018.v25.i01.p15, 2018)
This study aims to determine the effect of budgetary participation on budget slack with tight budget and locus of control as moderator. This research was conducted at 35 OPD in Badung regency. The method of determining the research sample using nonprobability sampling by purposive sampling, with the number of samples of 105 respondents. The data were collected by using questionnaires. Data analysis techniques used to test the hypothesis in this study is moderated regression analysis (MRA). The results of the analysis show that budget participation has a positive effect on budgetary slack. The results of the MRA analysis show that the tight budget weakens the effect of budgetary participation on budget slack, while the locus of control strengthens the influence of budgetary participation on budgetary slack Keywords: Participation, Tight, Locus of Control, Slack, Budget